2016
DOI: 10.1002/jsfa.7719
|View full text |Cite
|
Sign up to set email alerts
|

Iodide and iodate effects on the growth and fruit quality of strawberry

Abstract: The strawberry can be used as a target crop for iodine biofortification. Furthermore, applying an appropriate dose of KI can improve the fruit quality of the strawberry plants. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 18 publications
3
26
2
1
Order By: Relevance
“…Several authors found a positive effect of iodine applied to the nutrient solution on plant growth, especially if this element was supplied at low concentration and/or as IO 3 − (Borst Pauwels, 1961 on barley and tomato; Zhu et al, 2003 on spinach;Li et al, 2017 on strawberry). For example, Li et al (2017) reported an increase of plant biomass in strawberry when iodine was applied to the nutrient solution up to 1.97 μM as I − and 2.86 μM as IO 3 − . In contrast, detrimental effects were observed when the I − or IO 3 − concentrations in the nutrient solution were higher than 10-40 μM or 100-200 μM, respectively (Blasco et al, 2008).…”
Section: Discussion Effects Of Iodine On Plant Growthmentioning
confidence: 99%
“…Several authors found a positive effect of iodine applied to the nutrient solution on plant growth, especially if this element was supplied at low concentration and/or as IO 3 − (Borst Pauwels, 1961 on barley and tomato; Zhu et al, 2003 on spinach;Li et al, 2017 on strawberry). For example, Li et al (2017) reported an increase of plant biomass in strawberry when iodine was applied to the nutrient solution up to 1.97 μM as I − and 2.86 μM as IO 3 − . In contrast, detrimental effects were observed when the I − or IO 3 − concentrations in the nutrient solution were higher than 10-40 μM or 100-200 μM, respectively (Blasco et al, 2008).…”
Section: Discussion Effects Of Iodine On Plant Growthmentioning
confidence: 99%
“…Meanwhile, in tomato, Kiferle et al (2013) used high concentrations of 1 to 5 × 10 −3 M of KI and 0.5 to 2 × 10 −3 M KIO 3 in the nutrient solution once a week (eight times, starting with the fruit set of the first cluster), obtaining remarkable results, with an accumulation of iodine in the fruit of up to 10 mg of iodine per kg of fresh weight of fruit with little phytotoxicity. In strawberry plants, iodine increases plant biomass and fruit quality (Li et al, 2016). On the other hand, a decrease in biomass has been reported in tomato and potato (Caffagni et al, 2011), as well as in carrot (Smoleń et al, 2014b) and in Opuntia (García-Osuna et al, 2014), although in other plants where the vegetative reserve organs are also harvested, such as onion, iodine seems to have no effect on the weight of the plant (Dai et al, 2004b).…”
Section: Iodine Applications In Agricultural Cropsmentioning
confidence: 99%
“…On the other hand, iodine concentrations higher than 100 μM in the nutrient solution revealed an adverse effects on rice biomass (Mackowiak and Grossl, 1999; Singh et al, 2012), and in lettuce the same negative effect was observed by adding 40 μM of iodine (Blasco et al, 2008; Table 2). In strawberry plants, iodine in nutrient solution at concentrations of up to 1.97 × 10 −6 M (0.25 mg L −1 ) of I − and 2.86 × 10 −6 M (0.50 mg L −1 ) of IO3 increased the plant biomass and iodine concentration in fruits (Li et al, 2016). Thresholds for beneficial concentrations and toxicity of iodine are different between species, as a result of the inherent variability found among species and of the specific interaction of each plant species with edaphic, climatic, and biotic variables (Hageman et al, 1942; Mackowiak et al, 2005; Caffagni et al, 2012).…”
Section: Iodine Applications In Agricultural Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, results showed that the form and concentration of the microelement is crucial to achieve optimal biofortification without negative effects. For instance, IO3applied to strawberries cause nitrate accumulation, thus reducing food quality (Li et al 2017). Similarly, as in the case of iodine, the form and concentration of selenium applied onto plants is critical although it seems to be species-dependent.…”
Section: Foliar and Soil Fertilizationmentioning
confidence: 99%